Efektivitas Promosi Kesehatan melalui Demonstrasi terhadap Pengetahuan Kesehatan Gigi dan Mulut Lansia - Moh. Zikry Ariansyah Nayu; Bambang Hadi Sugito; I.G.A Kusuma Astuti N.P; Imam Sarwo Edi (Akademi Keperawatan Yarsi Samarinda, 2026)
Oral health issues remain a public health concern, particularly among the elderly. Limited knowledge regarding oral health maintenance places the elderly at risk for various oral diseases. One approach to improving this knowledge is through health promotion using the demonstration method. This study aimed to analyze the effectiveness of health promotion via the demonstration method on the oral health knowledge of the elderly. A pre-experimental design with a one-group pretest-posttest approach was employed. The study was conducted at the Garuda Elderly Integrated Health Post (Posyandu Lansia) in RW 10, Tambakrejo Village, Surabaya City, involving 45 respondents selected through simple random sampling. Data were collected using an oral health knowledge questionnaire administered before and after the intervention. Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Prior to the intervention, the majority of respondents fell into the